2012
DOI: 10.22358/jafs/66077/2012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linseed oil and selenate affect the concentration of fatty acids and selenium in the spleen, pancreas, and kidneys of lambs

Abstract: The purpose of the investigation was to determine the short-term influence of the addition of linseed oil (LO) and Se as selenate (SeVI) on the concentration of fatty acids (FA), especially conjugated linoleic acid (CLA) isomers, in the spleen, pancreas, and kidneys of lambs. The experiment was carried out on 20 lambs (25±2 kg) allotted to 4 groups of 5 animals each. For 35 days the lambs were fed a basal diet composed of concentrate and hay (control group; C) or supplemented with: 5% linseed oil (group LO), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…The relative increase in the concentration of C20:5n-3 in the fluids with LO and Se, especially as Se IV H or Se VI H, was higher than the relative increase in the concentration of αLNA in the fluids with LO and the higher concentration of Se IV or Se VI . This effect should be observed in in vivo investigations, resulting in an enhanced duodenal flow of αLNA or C20:5n-3 (Niedźwiedzka et al, 2008;Czauderna et al, 2010Czauderna et al, , 2012bKrajewska et al, 2012). Our observations are also consistent with recent in vivo and in vitro studies that have reported that the ruminal biohydrogenation of C20:5n-3 and other LPUFAn-3 was significantly lower compared to the ruminal biohydrogenation of C18-PUFA (e.g., LA or αLNA) (Dohme et al, 2003;Chow et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relative increase in the concentration of C20:5n-3 in the fluids with LO and Se, especially as Se IV H or Se VI H, was higher than the relative increase in the concentration of αLNA in the fluids with LO and the higher concentration of Se IV or Se VI . This effect should be observed in in vivo investigations, resulting in an enhanced duodenal flow of αLNA or C20:5n-3 (Niedźwiedzka et al, 2008;Czauderna et al, 2010Czauderna et al, , 2012bKrajewska et al, 2012). Our observations are also consistent with recent in vivo and in vitro studies that have reported that the ruminal biohydrogenation of C20:5n-3 and other LPUFAn-3 was significantly lower compared to the ruminal biohydrogenation of C18-PUFA (e.g., LA or αLNA) (Dohme et al, 2003;Chow et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…LPUFAn-3, abundantly present in fish oils, may provide a natural protection against biohydrogenation by the ruminal microorganisms (Burns et al, 2003;Chow et al, 2004;Wąsowska et al, 2006a;Buccioni et al, 2012). Recent studies revealed that selenate (Se VI ) or selenite (Se IV ) changed the contents of the FA, especially the CLA isomers and other conjugated FA, in the ovine ruminal fluid (Sieber et al, 2004;Wąsowska et al, 2006b;Czauderna et al, 2010Czauderna et al, , 2012a, the liver, muscles, internal organs and adipose tissues of animals (Czauderna et al, 2004a(Czauderna et al, , b, 2007Korniluk et al, 2006;Niedźwiedzka et al, 2008;Krajewska et al, 2012). Analysis of the selenium (Se) concentration of the microorganisms revealed that the ruminal microbial Se abundance was enriched relative to the level of Se in the diets.…”
mentioning
confidence: 99%
“…In fact, increasing contents of PUFAs, and especially n-3LPUFAs, in ruminant tissues is very important in view of the generally saturated nature of FAs in ruminant meats and the negative effect this can have on human health. Fortunately, amounts and types of fat and pro-or antioxidants added to the diet can influence the biohydrogenation yield of UFAs and the FA profiles in ruminant tissues (1,(4)(5)(6)(7). Our studies indicated that feeding linseed oil or FO effectively decreased the content of SFAs in tissues and increased the content of valuable monounsaturated FAs (MUFAs) and PUFAs (4).…”
Section: Introductionmentioning
confidence: 67%
“…Consequently, the percentage of undesirable FAs, like atherogenic and thrombogenic SFAs (A-SFA and T-SFA) (8) and especially C18:0, in tissues decreased, whereas the percentage of UFAs, particularly n-3LPUFAs, in tissues increased (1,9). However, the balance of UFAs, especially highly unsaturated FAs, prooxidants or antioxidants (e.g., Se-compounds or tocopherols), in feed is a critical factor influencing the quality of edible carcass parts of farm animals (4,7,10,11). Numerous studies showed that diets supplemented with selenized yeast (SeY) or selenate (SeVI) change the contents of FAs, tocopherols, and malondialdehyde (MDA; a marker of the oxidative stress) in animal tissues (4,7,9,11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation